DEVELOPMENT AND EVALUATION OF TRANSDERMAL GEL OF LORNOXICAM - Umar, Saifullahi; Onyekachi, Moh Kingsley (Universal Journal of Pharmaceutical Research, 2016)
Objective: Transdermal drug delivery systems deliver the drug through the skin at controlled rate to the systemic circulation. It maintains the blood concentration of the drug within the therapeutic system window ensuring that drug levels neither fall below the minimum effective concentration nor exceed the minimum toxic dose. The objective of the present work was to formulate transdermal gel of Lornoxicam. It is a COX-1 and COX-2 inhibitor used in the treatment of inflammation, pain and edema, rheumatoid arthritis. Methods: Transdermal gel of Lornoxicam was formulated using triethanolamine as solvent, HPMC K100 and EC as polymers. Formulated gel was evaluated with respect to different physiochemical parameters such as pH, viscosity, spreadability. In-vitro release study was performed for 10 hrs. Selected formulation was subjected to stability testing at different temperatures. Results: There was good homogeneity in all formulations and no lumps were present. The pH of the gel formulations was in the range of 6.77 to 7.14. Viscosity of various formulated gels was found in the range of 2176.5 to 3468.4 centipoises. The cumulative percent drug release after 10 hrs in between 50.3 to 82.11%. Accelerated stability studies for 12 weeks revealed that the transdermal gel formulation were stable at up to 45oC. Conclusion: Study concludes Lornoxicam can be delivered in the form of transdermal gel in an efficient way. On basis of drug content, particle size morphology, in-vitro release and stability studies, it can be concluded that formulation LTG4 was an optimum formulation. Peer Review History: Received 23 November 2016; Revised 6 January; Accepted 10 February, Available online 15 March 2017 Academic Editor: Dr. Amany Mohamed Alboghdadly , Princess Nourah bint abdulrahman university, Riyadh, amalbgadley@pnu.edu.sa Reviewer(s) detail: Prof. Dr. Syamsudin Abdillah , Pancasila University, Indonesia, syamsudin.abdillah@gmail.com Noha El Baghdady , MTI University, Cairo, Egypt, nohasalah21@yahoo.com